Мідний посуд та рис з Кам’янця-Подільського - Нечитайло, П.О.; Горбаненко, С.А. (Археологія, 2017)
Публікацію присвячено введенню до наукового обігу комплексу знахідок XVII ст. турецького походження з Кам’янця-Подільського. The publication aims to draw scholarly attention to a group of the 17th century objects of Turkish origin from KamianetsPodilskyi discovered in 2016 during the exploration of a foundry assemblage called Liudvisarni. The material was located in a layer of mixed loam with traces of a fire, full of broken brick «fingerings», ceramic floor tiles, fragments of kitchen and dining ceramics, a burnt tree and ashes. A «kitchen set» was found, consisting of four copper vessels: a large cooking pot, a pot with a handle (perhaps a frying pan), and two similar small «bowls» showing different levels of damage. Similar vessels to no. 1, 3, and 4 can be found in the collection of the 17th century Turkish copper dishes from Hungary, as well as in modern Turkey. Also noteworthy was the discovery of rice weevils from the burnt layer. Along with the pots, these findings indicate direct importation of copper vessels and rice. Consequently, the artefacts found in the enclosure between the southern (no. 2) and northern (no. 1) walls of the Turkish tower, as well as the palaeoethnobotanic materials, most likely refer to the time of Turkish garrison’s stay in Kamianets-Podilskyi during the period of the Podolia Eyalet (1672—1699). Публикация посвящена введению в научный оборот комплекса находок XVII в. турецкого происхождения из Каменец-Подольского, обнаруженного в 2016 г. во время исследований производственного литейного комплекса — Людвисарни. Материал находился в слое мешаного супесчаного грунта со следами пожара, насыщенного обломками кирпича «пальцовки», керамической плитки для пола, фрагментов кухонной и столовой керамики, горелого дерева и пепла. Обнаружен «кухонный набор», состоящий из четырех медных сосудов: котла, сосуда с ручкой (сковородки?), двух аналогичных «мисок» небольших размеров различной сохранности. Аналогии медным сосудам № 1, 3—4 известны в коллекциях медной турецкой посуды XVII в. из Венгрии и в современной Турции. Примечательна также находка зерновок риса, также происходящих из горелого слоя. В комплексе с посудой, эти находки свидетельствуют о прямом импорте медной посуды и риса. Таким образом, артефакты, обнаруженные в заполнении между южной (№ 2) и северной (№ 1) стенами Турецкой башни, а также палеоэтноботанические материалы, скорее всего, относятся к периоду пребывания в Каменце-Подольском турецкого гарнизона в период существования Подольского эялета (1672—1699 гг.).